2008
DOI: 10.2214/ajr.07.2559
|View full text |Cite
|
Sign up to set email alerts
|

Direct MR Arthrography of the Hip with Leg Traction: Feasibility for Assessing Articular Cartilage

Abstract: Hip MR arthrography with leg traction is a technically feasible and safe procedure that improves visualization of the femoral and acetabular cartilage surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 17 publications
0
54
0
2
Order By: Relevance
“…In radiology, axial traction is used as a ''carpal stress test'' in the diagnosis of scapholunate ligament injuries (16). Furthermore, four previous studies reported the advantages of applying axial traction during MR arthrography, one at the shoulder (9), two at the hip (10,17), and one at the knee (11). Llopis et al (10) noted greater distention of the hip joint with traction, leading to improved visualization of the femoral and acetabular cartilage surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In radiology, axial traction is used as a ''carpal stress test'' in the diagnosis of scapholunate ligament injuries (16). Furthermore, four previous studies reported the advantages of applying axial traction during MR arthrography, one at the shoulder (9), two at the hip (10,17), and one at the knee (11). Llopis et al (10) noted greater distention of the hip joint with traction, leading to improved visualization of the femoral and acetabular cartilage surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, four previous studies reported the advantages of applying axial traction during MR arthrography, one at the shoulder (9), two at the hip (10,17), and one at the knee (11). Llopis et al (10) noted greater distention of the hip joint with traction, leading to improved visualization of the femoral and acetabular cartilage surfaces. Palhais et al (11) found a slight but significant widening of the femorotibial joint space with traction, with a trend towards more contrast material separating the opposing cartilage surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The only slight increase in joint space width could be due to muscle contraction by the patient counteracting the traction force. As Llopis et al found a joint distension at the hip with only 6-kg traction [11], it could be possible, that 15 kg was too much traction leading to increased muscle contraction.…”
Section: Discussionmentioning
confidence: 98%
“…In the second study Nishii et al compared indirect MR arthrography of the hip with traction with standard MRI without traction in the evaluation of labral lesions and found a better accuracy of indirect MR arthrography with traction [12]; however, they did not compare indirect MR arthrography with and without traction. Recently Llopis et al evaluated direct MR arthrography of the hip with leg traction [11] and found an improved visualization of the femoral and acetabular cartilage surfaces owing to a better separation of these structures. To our knowledge no studies dealing with knee MR arthrography with traction were performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation